RUMAH ADAT MADURA: IDE KETERAMPILAN BERPIKIR VISUAL DARI TANEAN LANJHANG UNTUK PEMBELAJARAN MATEMATIKA - Nur Fadilah; Izzah Fijriyah; Indah Setyo Wardhani; Shintia Shepti Hariani; Novi Supriliyanti (Universitas Bhinneka PGRI, 2025)
The tanean lanjhang traditional house is a bridge between culture and visual thinking skills, as the shape, size and position of its architecture can be observed by our senses. The purpose of this study is to explore the idea of visual thinking skills from the tanean lanjhang traditional house that can be applied to mathematics learning. The type of research is qualitative research with the researcher as a participant. Data collection techniques are: observation, documentation, and literature study. The research instrument is an observation sheet that contains indicators of visual thinking skills and mathematical elements. The research subjects were 2 tanean lanjhang houses in Bangkalan and Pamekasan areas. The results concluded that in the tanean lanjhang traditional house, there are ideas of visual thinking skills in the form of visual reading skills, visual discrimination skills, social relationship observation skills, and visual closure skills. The implementation of the research can be applied in mathematics learning, such as in preparing mathematics teaching materials. LKPD and assessment.